Decoding the genetic and functional diversity of the DSF quorum-sensing system in Stenotrophomonas maltophilia - Huedo, Pol; Yero, Daniel; Martínez-Servat, Sònia; Ruyra, Àngels; Roher, Nerea; Daura, Xavier; Gibert, Isidre (Frontiers in Microbiology, 2015)
Stenotrophomonas maltophilia uses the Diffusible Signal Factor (DSF) quorum sensing (QS) system to mediate intra- and interspecific signalling and regulate virulence-related processes. The components of this system are encoded by the rpf cluster, with genes rpfF and rpfC encoding for the DSF synthase RpfF and sensor RpfC, respectively. Recently, we have shown that there exist two variants of the rpf cluster (rpf-1 and rpf-2), distinguishing two groups of S. maltophilia strains. Surprisingly, only rpf-1 strains produce detectable DSF, correlating with their ability to control biofilm formation, swarming motility and virulence. The evolutive advantage of acquiring two different rpf clusters, the phylogenetic time point and mechanism of this acquisition and the conditions that activate DSF production in rpf-2 strains, are however not known. Examination of this cluster in various species suggests that its variability originated most probably by genetic exchange between rhizosphere bacteria. We propose that rpf-2 variant strains make use of a strategy recently termed as “social cheating”. Analysis of cellular and extracellular fatty acids (FAs) of strains E77 (rpf-1) and M30 (rpf-2) suggests that their RpfFs have also a thioesterase activity that facilitates the release of unspecific FAs to the medium in addition to DSF. Production of DSF in rpf-1 strains appears in fact to be modulated by some of these extracellular FAs in addition to other factors such as temperature and nutrients, while in rpf-2 strains DSF biosynthesis is derepressed only upon detection of DSF itself, suggesting that they require cohabitation with DSF-producer bacteria to activate their DSF regulatory machinery. Finally, we show that the mixed rpf-1/rpf-2 population presents synergism in DSF production and virulence capacity in an in vivo infection model. Recovery and quantification of DSF from co-infected animals correlates with the observed mortality rate.